Guidelines for the diagnosis and treatment of knee osteoarthritis with integrative medicine based on traditional Chinese medicine - Zeng, Lingfeng; Zhou, Guanghui; Yang, Weiyi; Liu, Jun (Frontiers in Medicine, 2023)
Knee osteoarthritis (KOA) is a common geriatric disease in middle-aged and elderly people. Its main pathological characteristics are articular cartilage degeneration, changes in subchondral bone reactivity, osteophyte formation at joint edges, synovial disease, ligament relaxation or contracture, and joint capsular contracture. The prevalence rate of symptomatic KOA in middle-aged and elderly people in China is 8.1%, and this is increasing. The main clinical manifestations of this disease are pain and limited activity of the knee joint, which seriously affect the quality of life of patients and may cause disability, posing a huge burden on society and the economy. Although the pathogenesis of KOA is not clear, the treatment of KOA is diverse, and Chinese medicine, which mainly relies on plant-based natural products, has a relatively stable and reliable curative effect. This guideline aims to emphasize the evidence-based staging and stepped treatment of KOA and the therapeutic effect of integrative medicine based on traditional Chinese medicine on KOA. We make recommendations that include the adoption of manual therapy, acupuncture, external application of herbs, herbal plasters, exercise therapy, and other integrative medicine based on traditional Chinese medicine. Users of the above guidelines are most likely to include clinicians and health managers in healthcare settings.